Recent Progress of Marine Polypeptides as Anticancer Agents - Zheng, Lanhong; Xu, Yixin; Lin, Xiukun; Yuan, Zhixin; Liu, Minghua; Cao, Shousong; Zhang, Fuming; Linhardt, Robert J. (Recent Patents on Anti-Cancer Drug Discovery, 2018)
Background: Marine environment constitutes an almost infinite resource for novel anticancer drug discovery. The biodiversity of marine organisms provides a rich source for the discovery and development of novel anticancer peptides in the treatment of human cancer. Marine peptides represent a new opportunity to obtain lead compounds in biomedical field, particularly for cancer therapy. Objective: Providing an insight of the recent progress of patented marine peptides and presenting information about the structures and mechanistic mode of anticancer activities of these marine peptides. Methods: We reviewed recent progress on the patented anticancer peptides from marine organisms according to their targets on different signal pathways. This work focuses on relevant recent patents (2010-2018) that entail the anticancer activity with associated mechanism and related molecular diversity of marine peptides. The related cellular signaling pathways for novel peptides that induce apoptosis and affect tubulin-microtubule equilibrium, angiogenesis and kinase activity that are related to the anticancer and related pharmacological properties are also discussed. Results: The recent patents (2010-2018) of marine peptides with anticancer activity were reviewed, and the anticancer activity of marine peptides with associated mechanism and related molecular diversity of marine peptides were also discussed. Conclusion: Marine peptides possess chemical diversity and display potent anticancer activity via targeting different signal pathways. Some of the marine peptides are promising to be developed as novel anticancer agents.
Keywords: peptides/polypeptides